2012
DOI: 10.1056/nejmoa1200710
|View full text |Cite
|
Sign up to set email alerts
|

MYD88 L265P Somatic Mutation in Waldenström's Macroglobulinemia

Abstract: MYD88 L265P is a commonly recurring mutation in patients with Waldenström's macroglobulinemia that can be useful in differentiating Waldenström's macroglobulinemia and non-IgM LPL from B-cell disorders that have some of the same features. (Funded by the Peter and Helen Bing Foundation and others.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

39
858
2
18

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,136 publications
(947 citation statements)
references
References 34 publications
39
858
2
18
Order By: Relevance
“…11 Mutations of MYD88, including the L265P point mutation, had been previously described in diffuse Figure 2 Three cases of small B-cell neoplasm with plasmacytic differentiation, not otherwise specified, with MYD88 mutations displayed diffuse architectural effacement (a) by a monomorphic lymphoplasmacytic infiltrate (b) cytologically similar to that seen in classic lymphoplasmacytic lymphoma.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…11 Mutations of MYD88, including the L265P point mutation, had been previously described in diffuse Figure 2 Three cases of small B-cell neoplasm with plasmacytic differentiation, not otherwise specified, with MYD88 mutations displayed diffuse architectural effacement (a) by a monomorphic lymphoplasmacytic infiltrate (b) cytologically similar to that seen in classic lymphoplasmacytic lymphoma.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, next generation sequencing studies have identified a highly recurrent point mutation, MYD88 L265P, in 490% of cases of bone-marrow-based lymphoplasmacytic lymphoma/Waldenstrom's macroglobulinemia, [11][12][13][14][15][16] suggesting that this mutation may serve as a sensitive diagnostic marker for lymphoplasmacytic lymphoma. A previous study has suggested that detection of the MYD88 L265P abnormality can assist in classifying challenging bonemarrow-based B-cell neoplasms with plasmacytic differentiation.…”
mentioning
confidence: 99%
“…14,24,25 For instance, it was recently described that an oncogenic-activating mutation of MyD88 is responsible for the uncontrolled proliferation of cells from patients affected by lymphomas and Waldenström's macroglobulinemia, a subgroup of immunoglobulin M-secreting non-Hodgkin lymphomas. In both studies, treatment of patient cells with the MyD88 decoy epta-peptide strongly inhibited oncogenic proliferation in vitro, 13,14 which suggests that MyD88 inhibitors could be therapeutically suitable for these neoplastic diseases. This is particularly relevant for patients with Waldenström's macroglobulinemia, because a mutation of MyD88 was found in the large majority of patients affected by this neoplasia.…”
Section: Application Of Myd88 Inhibitors To Models Of Human Diseasesmentioning
confidence: 99%
“…9,10 Notably, MyD88 itself was shown to play a determinant role in the promotion of several human cancers, including blood malignancies such as lymphoma and chronic lymphocytic leukemia. [11][12][13][14][15] For these reasons, the TLR/IL-1R pathway has attracted considerable interest as a potential therapeutic target. 16,17 …”
Section: Introductionmentioning
confidence: 99%
“…43 Of interest diagnostically, it is found in only a small proportion of marginal zone lymphomas and CLL but present in about 90% of lymphoplasmacytic lymphomas, suggesting we may finally have a diagnostic tool with a high yield to help make the latter diagnosis. 35,43,44 The sequencing technologies can also be used to identify chromosomal translocations.…”
Section: Molecular Studiesmentioning
confidence: 99%